(untitled) (AYUSHDHARA, 2021)
The term Geriatrics is made by union of two Greek word first ‘geras’ (old age) and second ‘iatros’ (physician) and derived from Greek root “gergero- geronto” meaning old age or the aged or especially one receiving special care. Geriatrics is the branch of medicine that focuses on health promotion and prevention and treatment of disease and disability in later life. In India population of the elderly has been increasing steadily since 1961 as it touched 13.8 crore in 2021, growing faster due to decrease in death rate, according to a study by National Statistical Office (NSO). Ageing is the process in which structural and functional changes occur with passage of time. Thus study of all aspects of ageing including physiological, pathological, psychological, economical and sociological problems is termed as Geriatrics. With advancing age, several changes take place in the body, in the external appearance as well as in Dosha, Dhatu, Mala, Agni, Oja level, also on the mental functions. In Ayurvedic texts, there are many ways given for prevention and promotion of health, one of them is Dinacharya (daily regimen), which is most important part to maintain a healthy and happy life. The importance of appropriate daily routine cannot be underestimated. It set the wheels in motion for entire day, bringing a sense of calm and well-being. It gives the body, mind and spirit the chance to start afresh.